Children's film in the digital age essays on audience, adaptation and consumer culture - Beeler, Karin 1963-; Beeler, Stanley W. 1954- (McFarland & Company, Inc., Publishers, 2015)
"This collection of new essays explores how children's film can be re-examined alongside recent developments in their production. These analyses consider the effect of multimedia strategies on the child audience, and the opportunities for participation and their pedagogical implications. The essays also address how childhood is embedded within films and linked to various consumer contexts"..
Literaturangaben
Keywords: Children's films -- History and criticism; Film adaptations -- History and criticism; Childhood in motion pictures; Neue Medien; Kinderfilm; Aufsatzsammlung